Analysis of anxiety in young adults resulting from the COVID-19 pandemic (Research, Society and Development, 2022)
The article presents an analysis of the concern of young adults expressed by the pandemic. This phase of human development corresponds to a part of the population that is more active in society, at this stage more interaction with the environment, and the “I” is in full formation. Over time, it was possible to observe the importance of recognizing the ecologically correct impacts that reached the epidemic by the population, including the COVID-19 pandemic, and the need to change and adapt to a new social, affective and affective reality. behavior, based on this information, the objective was to investigate the anxiety levels of young people in the pandemic, resulting from SARS-CoV-2. The study of pandemic in question of a crisis and how a new outbreak of stress in an emergency situation and how stress situations in quarantine, in a state of quarantine, if one of the dam attempts or in a disease epidemic was tested, generating fear and misinformation. As exposure to social isolation issues, concern about fear of isolation is presented by the numbers of social isolation symptoms presented by the numbers of isolation symptoms of the unique numbers of social isolation symptoms. Where, the results show that professionals who maintain contact with the infected may have higher levels of anxiety, depression and stress. In this way, we conclude the need for the Federative States, to invest in assistance, for the population, in order to promote health solutions, for environmental health problems, for health problems, for environmental benefits, so that Anxiety, in this period.